Pengaruh Pendidikan Kesehatan Jiwa Terhadap Pengetahuan Keluarga Pada Pasien Dengan Gangguan Jiwa Di PUSKESMAS Banguntapan I - Wati, Unik Setia; Melina, Fitria (Jurnal Kesehatan Samodra Ilmu (JKSI), 2025)
Background: Mental disorders are a global health problem with a broad impact, not only on individuals but also on families and communities. The WHO reports that more than 970 million people suffer from mental disorders worldwide, and Indonesia has a prevalence of schizophrenia of 7 per 1,000. The Special Region of Yogyakarta ranks first with the highest prevalence of severe mental disorders (9.3%), with Bantul Regency having 2,999 people with mental disorders. Lack of family knowledge regarding the symptoms, causes, and treatment of patients with mental disorders contributes to inappropriate treatment and social stigma. A preliminary study at the Banguntapan I Community Health Center (Puskesmas I) revealed 55 individuals with mental disorders between January and July. Research Methods: This study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest approach. A total of 55 respondents from families of patients with mental disorders were selected using a total sampling method. The intervention consisted of health education and leaflets. The instrument was a questionnaire to assess the level of knowledge. Univariate analysis was used to describe the frequency and percentage of knowledge levels before and after the intervention. Bivariate analysis using the Wilcoxon test was conducted to assess the effect of mental health education on family knowledge Research Results: Before mental health education, the majority of respondents' knowledge was in the poor category (45 respondents (81.8%). After mental health education, the majority of respondents' knowledge was in the good category (55 respondents (100%). The Wilcoxon test showed a p-value of 0.000, indicating a significant effect of mental health education on improving family knowledge. Conclusion: There is an effect of health education on family knowledge at Banguntapan I Community Health Center, as indicated by the bivariate test using Wilcoxon, with a Z-value of 6.446 and a p-value of 0.0000 (p<0.05).